THU0348 The Influence of Drug Exposures and Comorbidity on Survival in Patients with Rheumatoid Arthritis. (9th June 2015) - Widdifield, J.; Abrahamowicz, M.; Paterson, M.; Bombardier, C.; Tomlinson, G.; Huang, A.; Kuriya, B.; Bernatsky, S.
Abstract : Background: Patients with rheumatoid arthritis (RA) have an increased mortality compared with the general population. 1 Established risk factors for premature mortality include active inflammation/disease activity, comorbidity and extra-articular disease manifestations. Thus, early and greater exposure to disease-modifying anti-rheumatic drugs (DMARDs) may mitigate these risk factors and improve survival in RA. Objectives: Our aim was to evaluate the associations between RA drug exposures and survival in seniors with incident RA. Methods: This retrospective cohort study investigated all incident cases of RA diagnosed from 2000 to 2013. We studied a subset of patients within the Ontario RA Database (ORAD) - a validated population-based cohort of all Ontarians with RA - who were aged 66 years and older who have comprehensive public drug insurance. We used Cox proportional hazards regression to investigate mortality, defined as death from any cause, exploring time-dependent cumulative drug exposures during the entire duration of follow-up, while adjusting for baseline age, sex, urban vs. rural residence, socioeconomic status, pre-existing comorbidities (e.g. hypertension, COPD, diabetes, coronary artery disease, cancer), past drug exposures, time-dependent number of physician visits, and extra-articular manifestations of RA (as proxies for RA severity). Adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated. Results: Among 25, 416 senior RA patients, 67.8% were female, the mean (SD) age was 75.2 (6.5) years, and 85.4% lived in urban areas. During median and maximum follow-up times of 4.4 and 13.2 years, respectively, 7, 956 patients died (31.3%) for a mortality rate of 6.2 per 100 person-years. In multivariable analyses, we observed no association between greater cumulative exposure to methotrexate, other DMARDs, or anti-TNF agents and survival. Greater exposure to corticosteroids was associated with greater risk of mortality [HR 1.15 (95% CI 1.14-1.17)], as were greater baseline comorbidity [Charlson HR 1.36 (95% CI 1.34-1.38)] and extra articular disease [HR 1.53 (95% CI 1.47, 1.61)]. Females and residents living in urban areas had lower mortality risk [HR 0.78 (95% CI 0.75-0.82) and HR 0.92 (95% CI 0.86-0.98), respectively]. Conclusions: Though we could not demonstrate an association between exposure to DMARDs and over-all survival in seniors with RA, cause-specific mortality warrants further investigation. Greater exposure to corticosteroids, comorbidity and extra articular RA was associated with pre-mature mortality in our sample. References: Widdifield et al, Trends in Excess Mortality among Patients with Rheumatoid Arthritis in Ontario, Canada. Arthritis Care & Research 2015 [in press]. Disclosure of Interest: None declared